15 Characterization of an aSi-1000 EPID response in integrated and continuous acquisition modes for SBRT dosimetry applications. (December 2018) - Barbeiro, A.R.; Parent, L.; Chatrie, F.; Ferrand, R.; Younan, F.; Simon, L.; Vieillevigne, L.; Lazaro, D.; Tromson, D.; Cunrath, A.L.; Le Lann, M.V.; Mazurier, J.; et al.
Abstract : Introduction: The amorphous silicon (a-Si) electronic portal imaging devices (EPIDs) mounted on linacs have been extensively studied and have shown dose-response characteristics suitable for dose verification. Their use for dosimetric purposes is already in clinical routine. However, the response of EPID in continuous acquisition mode was not so studied in literature, and in less extent when considering it for dosimetric applications in stereotactic body radiotherapy (SBRT) conditions (i.e. small fields, and high dose rates using flattening filter free (FFF) beams). The purpose of this work was therefore to characterize the EPID response in terms of relevant dosimetric properties, mainly for the potential use of continuous mode for further SBRT dosimetry with dynamic techniques. Methods: The EPID used in this study was the aSi-1000 model installed on a Varian TrueBeamSTx. Its response was characterized in FFF photon beams with nominal energies of 6 and 10 MV and maximum available dose rates (1400 and 2400 MU/min, for 6 and 10 MV respectively). Different sets of images were acquired in both integrated and continuous modes, with EPID at 150 cm from the source, to study dose linearity, repeatability and reproducibility of response, field-size dependence, ghosting effect and response to energy spectrum variations. Before data acquisition, dark field and flood filed images were acquired for offset and gain corrections. As fluctuations in dose rate can potentially influence the response of EPID when using dynamic techniques with continuous acquisition mode, the linearity of EPID response was further evaluated by irradiating a 10 × 10 cm 2 field in 20° and 90° arcs focusing on low MU range (3–100 MU), and was also compared to static irradiations. Results: Generally, comparable results in terms of dose response linearity, and signal stability for both acquisition modes were obtained, although slightly better for integrated mode. As example, the comparison of EPID response-to-MU ratios for both modes and for the evaluation using the arc field is presented in Fig. 1, for the 6MV FFF. Variations in linearity response were within 2.5% and 2.9%, respectively for the integrated and continuous mode, at lower MUs. Conclusions: The characterization of the aSi-1000 EPID response to relevant dosimetric properties was investigated, showing the feasibility of its use for dosimetry with FFF beams and high dose rates. Results for continuous mode, which differed from dosimetric non-linearity reported in previous published studies[1], also encourage the use of EPID for SBRT with dynamic techniques in future works for 3D dosimetry applications (e.g. quality assurance including in vivo dosimetry).